From Domination to Dialogue and the Ethics of the Between: Transforming Human-Working Equine Relationships in Mountain Tourism - Cousquer, Glen (Austral Journal of Veterinary Sciences, 2023)
The welfare of working equines is born of the relationship co-created with humans and the relational practices humans bring to this work. Our understanding of this relationship remains elusive, however, for it involves attending to that which arises both within and between the equine and the human. Attempts to study such relationships have, arguably, been confounded by the liminalities of relational practices, power literacy and the limitations of language, propositional knowing and the dualistic thinking that characterises many scientific disciplines. This paper presents the theoretical framework that underpins an experiential awareness-based Action Research approach to transforming human-equine relations within the international mountain tourism industry. This approach privileges curiosity, compassion and primary or contemplative knowing and the development of self-awareness. Drawing on the work of Martin Buber on genuine dialogue and of Otto Scharmer on generative dialogue, this paper provides insights into what can arise in the between when attitudinal shifts are encouraged and facilitated that allow humans and equines to meet genuinely and be fully present to each other. This ultimately involves surrendering control, letting go, the dissolution of subject-object awareness and access to non-dualistic ways of knowing. An awareness of the importance of such shifts and of the source from which we operate is of fundamental importance to the realisation of the co-creative project that humans and equines can engage in. Failure to appreciate this distinction, arguably, leads and gives rise to relationships, whether human-to-human or human-to-horse, characterised by domination rather than partnering, absencing rather than presencing, by monologue rather than dialogue. The ethical and practical implications of this awareness are profound, with implications felt at the level of the individual, for whom the I deepens the more you pay attention, and at the level of the relationship, but also at the level of communities, whether these be constituted locally, nationally, internationally or indeed globally.